The Portrait of the Prophet Muhammad (peace be upon him) in the Persian Poems of Mustafa Begi Kurdî - سعید, عمر محمد (Sulaimani Journal for Humanities, 2020)
The article presents Mustafa bag Sahebqran’s attitude towards the prophet of Islam Muhammed. In his great Persian poims Sahebqran reveals his praise towards him in his poims. As the last apostle Sahebqran shows the prophet muhammed blessings of God and bunch of ( peace be upon him ) who mnifests the message of heaven to the humanity. The poet in his poems praises the prophet and shows him as an acumen person who could bravely and wisely push humanity towards charity and morality.
Keywords: Praise of the Prophet (peace be upon him); Quranic verses; Prophetic traditions; Votesof elders; Poetry Court Kurdi